A new numerical model for understanding free and dissolved gasprogression toward the atmosphere in aquatic methane seepage systems - Jansson, Pär; Ferré, Benedicte; Silyakova, Anna; Dølven, Knut Ola; Omstedt, Anders (Limnology and Oceanography: Methods, 2019)
Source at https://doi.org/10.1002/lom3.10307 . We present a marine two‐phase gas model in one dimension (M2PG1) resolving interaction between the free and dissolved gas phases and the gas propagation toward the atmosphere in aquatic environments. The motivation for the model development was to improve the understanding of benthic methane seepage impact on aquatic environments and its effect on atmospheric greenhouse gas composition. Rising, dissolution, and exsolution of a wide size‐range of bubbles comprising several gas species are modeled simultaneously with the evolution of the aqueous gas concentrations. A model sensitivity analysis elucidates the relative importance of process parameterizations and environmental effects on the gas behavior. The parameterization of transfer velocity across bubble rims has the greatest influence on the resulting gas distribution, and bubble sizes are critical for predicting the fate of emitted bubble gas. High salinity increases the rise height of bubbles; whereas temperature does not significantly alter it. Vertical mixing and aerobic oxidation play insignificant roles in environments where advection is important. The model, applied in an Arctic Ocean methane seepage location, showed good agreement with acoustically derived bubble rise heights and in situ sampled methane concentration profiles. Coupled with numerical ocean circulation and biogeochemical models, M2PG1 could predict the impact of benthic methane emissions on the marine environment and the atmosphere on long time scales and large spatial scales. Because of its flexibility, M2PG1 can be applied in a wide variety of environmental settings and future M2PG1 applications may include gas leakage from seafloor installations and bubble injection by wave action.